ChemInform Abstract: Hyrtimomines, Indole Alkaloids from Okinawan Marine Sponges Hyrtios spp. Issue 28 (15th July 2014) - Tanaka, Naonobu; Momose, Rei; Takahashi‐Nakaguchi, Azusa; Gonoi, Tohru; Fromont, Jane; Kobayashi, Jun'ichi
Abstract Six new indole alkaloids, hyrtimomines F‐K, are isolated and screened for their antimicrobial activities.